Christian Communication, Forms, Secularity, and Dimensions of Language in a Multifaceted Cultural Setting - Adebayo, Rufus; Zulu, Sylvia (African Journal of Inter/Multidisciplinary Studies, 2021)
Christian communication and the various dimensions of language are profoundly connected and interchangeably used in a multifaceted cultural setting. Christian churches in South Africa, similar to any other African countries, profess their philosophies, passions, and beliefs to multi-cultural congregations through the use of sacred languages and communication. This study posits that the uprising of Pentecostal churches has paved the way for nonspiritual dialectic languages and has also greatly lessened spiritual communication. As a result, the study highlights the relationship between language and religious communication among Pentecostal churches in a culturally diverse environment. This study employs a qualitative approach, through the gathering and categorisation of information between 20 churches located in Durban, South Africa to recognise Christian communication and the influence of secular linguistic features and their relationships with spirituality. This study has found that there are different forms and secular dimensions of language which differ from spiritual language and Christian communication. The study reveals that as modern Christian churches emerge, a revolutionised communication has evolved as compared to the language of orthodox churches. The study recommends that the use of language for religious communication and discourse should necessitate expounding spiritual values and courses of action.